2020
DOI: 10.3390/joitmc6040183
|View full text |Cite
|
Sign up to set email alerts
|

Portugal’s Changing Defense Industry: Is the Triple Helix Model of Knowledge Society Replacing State Leadership Model?

Abstract: The defense industry has unique features involving national sovereignty. Despite the characteristics that led to the separation of the military and civil spheres, since the 1990s, the number of dual-use projects has been growing. Taking into account that Portugal is a small European country, this paper analyzes the relationships within the defense industry in order to determine how university–industry–government relationships (the Triple Helix) function in this specific industry. The analysis of 145 projects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 60 publications
2
11
0
Order By: Relevance
“…In addition to cooperation between military entities and the business community, the production of knowledge in universities opens doors to other innovation and technological development (I&DT) projects, scientific production Rana 2019, 2020), and the development of patents (Ayerbe et al 2014). The argument above aligns with Simões et al (2020) article, who analysed 145 projects of the Portuguese Ministry of Defence and found that academia represented more than 90% of the projects, 40% of those have a dual-use application. The defence industry also has some specificities when compared to the civil industrial sector, mainly regarding strategic alliances.…”
Section: Findings From the Case Researchsupporting
confidence: 63%
See 2 more Smart Citations
“…In addition to cooperation between military entities and the business community, the production of knowledge in universities opens doors to other innovation and technological development (I&DT) projects, scientific production Rana 2019, 2020), and the development of patents (Ayerbe et al 2014). The argument above aligns with Simões et al (2020) article, who analysed 145 projects of the Portuguese Ministry of Defence and found that academia represented more than 90% of the projects, 40% of those have a dual-use application. The defence industry also has some specificities when compared to the civil industrial sector, mainly regarding strategic alliances.…”
Section: Findings From the Case Researchsupporting
confidence: 63%
“…This article builds upon the existing theory (Simões et al 2020), seeking to explore the defence industry in what is known as the quintuple helix innovation model. Thus, this article goes beyond the recent findings of Reis (2021) that suggest a possible existence of quadruple helix within the scope of the defence industry.…”
Section: Contributions To Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…The first stage was qualitative, exploratory research based upon semi-structured interviews, followed by quantitative research using a questionnaire (S1 File) in the second stage. The questionnaire asked about the changes that would be necessary for the companies' quality systems to enhance multigenerational learning and knowledge preservation [46,47].…”
Section: Methodsmentioning
confidence: 99%
“…Departing from the Triple Helix adaptability and the perspective that the model will adjust to societal changes (theories and perspectives established in previous sections) in Chapter 5 we engage with the discussions promoted by Amaral and Cai (2022) on the relations between the different Helix models to establish that of a couple of academic publications giving attention to relations within the boundaries of the institutional spheres (Lee and Kim, 2016;Simões, Moreira, and Mendes Dias, 2020) were not adequately addressed in the existing Triple Helix conceptual framework. Identifying this situation as the focal point of departure (Jaakkola, 2020) the conceptual argument develops using a multidisciplinary approach leverage in kinematics, and Triple Helix adaptability, to propose taking advantage of different reference frameworks (scopes) to expand and enhance the Triple Helix model into an endless perspective.…”
Section: Methodsmentioning
confidence: 99%